2018
DOI: 10.1016/j.bbamem.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary docosahexaenoic acid on rhodopsin content and packing in photoreceptor cell membranes

Abstract: Docosahexaenoic acid (DHA) is enriched in photoreceptor cell membranes. DHA deficiency impairs vision due to photoreceptor cell dysfunction, which is caused, at least in part, by reduced activity of rhodopsin, the light receptor that initiates phototransduction. It is unclear how the depletion of membrane DHA impacts the structural properties of rhodopsin and, in turn, its activity. Atomic force microscopy (AFM) was used to assess the impact of DHA deficiency on membrane structure and rhodopsin organization. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 61 publications
1
42
1
Order By: Relevance
“…Another important conclusion from our study is that the consequences of DHA deficit caused by the Mfsd2a knock-out are different from those caused by dietary DHA restriction. Dietary restriction in mice and rats could lead to a higher degree of DHA deprivation of the retina associated with reductions in ERG responses, outer segment shortening and alteration in the rate of photoreceptor outer segment renewal without notable photoreceptor loss (Benolken et al, 1973;Wheeler et al, 1975;Senapati et al, 2018). However, this diet leads to a major substitution of DHA with docosapentaenoic acid (22:5; Anderson et al, 1974;Niu et al, 2004), which does not happen in Mfsd2a Ϫ/Ϫ retinas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important conclusion from our study is that the consequences of DHA deficit caused by the Mfsd2a knock-out are different from those caused by dietary DHA restriction. Dietary restriction in mice and rats could lead to a higher degree of DHA deprivation of the retina associated with reductions in ERG responses, outer segment shortening and alteration in the rate of photoreceptor outer segment renewal without notable photoreceptor loss (Benolken et al, 1973;Wheeler et al, 1975;Senapati et al, 2018). However, this diet leads to a major substitution of DHA with docosapentaenoic acid (22:5; Anderson et al, 1974;Niu et al, 2004), which does not happen in Mfsd2a Ϫ/Ϫ retinas.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that, like the brain, the retina cannot synthesize its own DHA de novo and relies on uptake from extraretinal sources, such as blood-borne lipids, for maintaining its DHA content (Scott and Bazan, 1989;Bazan et al, 2011). Multiple studies analyzing the consequences of DHA dietary restriction documented that DHA-deprived retinas produced light responses of reduced sensitivity (Benolken et al, 1973;Wheeler et al, 1975;Senapati et al, 2018), suggesting that DHA may be critical for supporting visual signaling. Recently, Silver and colleagues showed that Mfsd2a is expressed in retinal pigment epithelium (RPE) and retinal vasculature and that the Mfsd2a-mediated lipid transport in RPE is particularly important for maintaining the high DHA concentration in the retina (Wong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…First, a member of the phospholipid flippase family has been shown to be essential for odourant receptor responses in Drosophila melanogaster 44,45 , suggesting that the PL composition of the OSN plasma membrane is an important factor for olfactory signalling. A number of studies also demonstrated that DHA-rich retinal PLs enhance the activity of rhodopsin, a receptor that belongs to the same G-protein-coupled receptor class as odourant receptors [46][47][48][49][50][51][52][53] . Specific interactions between DHA and rhodopsin improve the stability of the receptor 54 .…”
Section: Con L Owmentioning
confidence: 99%
“…OS is heavily loaded with a large number of closed membranous sacs, which overlap as pancakes stacked in a perpendicular array respect to the major axis of the rod. Rhodopsin and others GPs visual pigments move along and within (flip-flop) the phospholipid bilayer thus being their functionality fully dependent of the viscosity/fluidity balance of the sacs membranes, fact which in turns is mainly determined for the relative ratio of ω3/ω6 /ω9 PUFAs and cholesterol [81, 82]. Rods are distributed by the retina together with the cones but are better adapted for vision with little light intensity or twilight vision (scotopic vision), which does not allow a proper the perception of colors.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 3). DHA and other ω3 and ω6 LCHU-PUFAs are separated and esterified in triglycerides, stored in the abundant oil droplets of PEC and then re-uptaked by myoid area of rod and cones [8, 12, 82, 103, 104].…”
Section: Introductionmentioning
confidence: 99%